The Influence of Promotion Through Social Media on Middle-Class Consumer Decisions at The Hair Loft Surabaya Barbershop - Endra Wahyu Septianan, Sofyan Lazuardi, Kuswandi (Social Sciences Journal, 2025)
The rapid growth of the service industry in Indonesia, particularly in the men's grooming sector, has intensified competition among barbershops. In this context, promotion through social media has become one of the most effective strategies for attracting and retaining customers, especially middle-class consumers who are highly concerned about lifestyle and appearance. This study aims to analyze the influence of social media promotions on middle-class consumer decisions at The Hair Loft Barbershop in Surabaya. This study used an exploratory qualitative method, with data obtained through in-depth interviews, observations, and surveys involving middle-class consumers who use The Hair Loft's services and actively engage with its social media content. This study focused on how visual content, discount information, testimonials, and online interactions shape consumer perceptions, attitudes, and purchasing decisions. The findings indicate that social media promotions significantly influence consumer decisions. Most respondents reported first learning about The Hair Loft through Instagram before deciding to visit. Factors such as visual appeal, clear promotional information, barber professionalism, and alignment with lifestyle trends were found to be key determinants of consumer decision-making. Furthermore, the intensity of promotional exposure on social media is closely related to consumer loyalty, as frequent interaction with digital content encourages repeat visits. In conclusion, social media promotion not only serves as an effective communication tool to attract new customers but also plays a strategic role in building consumer loyalty. For The Hair Loft Barbershop, consistent, creative, and consumer-oriented social media content is crucial for strengthening branding, maintaining competitiveness, and ensuring long-term business sustainability in the men's grooming industry.Keywords: Barbershop, Consumer Decisions, Middle-Class Consumers, Social Media Promotion, The Hair Loft Surabaya